Chinese herbal medicine Xiaoji decoction inhibited growth of lung cancer cells through AMPKα-mediated inhibition of Sp1 and DNA methyltransferase 1. (2nd April 2016) - Zhao, ShunYu; Wu, Jingjing; Tang, Qing; Zheng, Fang; Yang, LiJun; Chen, YuQin; Li, Liuning; Hann, Swei Sunny
Abstract: Ethnopharmacological relevance: Xiaoji decoction (XJD), which was considered as a Chinese herbal prescription, has been used for cancer treatment, especially lung cancer, for decades to improve quality of life and prolong the patient survival. However, the molecular mechanisms underlying the therapeutic potential have not been well elucidated. Materials and methods: The cell viability was examined by MTT assays. The phosphorylation and expression of AMP-activated protein kinase alpha (AMPKα), DNA methyltransferase 1 (DNMT1) and transcription factor Sp1 proteins were assessed by Western Blot. Exogenous expression of Sp1 and DNMT1 were performed by transient transfection methods. The effects of XJD on the growth of xenograft tumors were evaluated by in vivo bioluminescence imaging. Results: We showed that XJD inhibited growth of human non small cell lung cancer (NSCLC) cells in vitro. We also found that XJD increased phosphorylation of AMPKα and inhibited protein expression of DNTM1, the latter was not observed in the presence of the inhibitor of AMPK (compound C). Overexpression of DNTM1 reversed the effect of XJD on cell growth. In addition, XJD decreased Sp1 protein expression, which was eliminated by compound C. Conversely, exogenous expressed Sp1 abrogated XJD-inhibited DNTM1 protein expression. Interestingly, exogenous expression of DNMT1 feedback antagonized the XJD-induced phosphorylation of AMPKα. In in vivo studies, we found that XJD inhibited tumor growth in xenograft nude mice model, which was accompanied by induction of phosphorylation of AMPKα and suppression of DNMT1 protein from xenograft tumors. Conclusion: Our results show that XJD inhibits NSCLC cell growth via AMPKα-mediated inhibition of transcription of Sp1, followed by the reduction of DNMT1 expression both in vitro and in vivo. The negative feedback regulation loop of AMPKα further demonstrates the critical role of DNMT1 in mediating the overall effects of XJD in this process. This study unveils novel molecular mechanism by which XJD controls NSCLC cell growth. Graphical abstract: